Trustworthy Digital Forensics in the Cloud. - Zawoad, Shams; Hasan, Ragib (Computer (00189162), 2016)
Digital forensics is used to help investigate cybercrime. Because of its characteristics and rapid adoption, the cloud requires its own form of forensics, which must be reliable. The authors have developed the Open Cloud Forensics (OCF) model and FECloud architecture, which would enable effective cloud forensics.